Remodelling of the gut microbiota by hyperactive NLRP3 induces regulatory T cells to maintain homeostasis - Xiaomin Yao (Nature Portfolio, 2017)
Inflammasomes are involved in gut homeostasis and inflammatory pathologies. The authors show that a hyperactive NLRP3 inflammasome maintains gut homeostasis through remodelling of the gut microbiota and induction of regulatory T cells.